Agronomic Rice Practices and Postharvest Processing : Production and Quality Improvement - Verma, Deepak Kumar; Srivastav, Prem Prakash; Nadaf, Altafhusain B.; Taylor and Francis (Boca Raton, FL : Apple Academic Press, 2018)
This volume addresses three important agricultural aspects of rice: physical characteristics, physico-chemical characteristics, and the organoleptic aspects. Divided into sections, the book first examines recent trends and advances for higher production and quality improvement, focusing on the effects of climate on rice cultivation and climate-resilient agricultural practices in rice. The volume goes on to cover nutrient management for rice production and quality improvement. Chapters also address weed management and postharvest processing practices for improved rice production. With chapters from renowned scientists, researchers, and professors, this book will be a useful reference for rice researchers working in the area of agronomic practices, postharvest processing, and quality improvement in rice.
Climate-Resilient Agricultural Practices in Rice: An Indian Perspective -- Arnab Banerjee and Manoj Kumar Jhariya -- Direct Seeded vs Transplanted Rice in Asia: Climatic Effects, Relative Performance, and Constraints, A Comparative Outlook -- Umair Ashraf, Zhaowen Mo, and Xiangru Tang -- Temperate Rice Culture: Constraints and Interventions to Mitigate the Challenges -- Asif B. Shikari et al. -- System of Rice Intensification (SRI): Recent Advances and Trends -- Ashaq Hussain, Parmeet Singh, and Aabid Hussain -- Lone Effect of Zinc (Zn) on Growth, Yield and Quality Attributes of Rice (Oryza sativa L.) for Improved Rice Production -- V. K. Verma, Deepak Kumar Verma, and Ram Kumar Singh -- Integrated Nutrient Management (INM) in Transplanted Rice by the Pelleting Technique -- Manish Kumar Sharma and Parmeshwar Kumar Sahu -- Integrated Nutrient Management (INM): Potential Practices for Rice Productivity and Yield -- Deepak Kumar Verma et al. -- Integrated Weed Management (IWM) Practices in Zero-Till Direct Seeded Rice (DSR) -- Gaurav S. K. Verma et al. -- Effect of Parboiling on Different Physico-Chemical and Cooking Properties of Rice -- Deepak Kumar Verma et al. -- Nutritional Quality Evaluation of Different Rice Cultivars -- Deepak Kumar Verma, Prem Prakash Srivastav, and Mukesh Mohan.
Includes bibliographical references and index.
Also available in print format.
Keywords: Rice; Electronic books